Preaching to the Empty Pew: The Lived Experiences in Preaching among Seventh-day Adventist Pastors during the COVID-19 Pandemic in Singapore - Kaumpungan, Margihon Bayu Putra (Klabat Theological Review; Vol 3 No 2 (2022): Klabat Theological ReviewDO - 10.31154/ktr.v3i2.868.116-126, 2022)
Preaching is fundamental to the ministry of a pastor. It is the heart of pastoral service anywhere. Challenges in preaching and novel approaches in homiletical arts have been extensively studied. However, the COVID-19 pandemic brought a new paradigm to the field of homiletics that is worthy of investigation. This study is a pilot project investigating the experience of Seventh-day Adventist pastors preaching during the pandemic. The loss of human interaction, adaptation to technology, the change of duration, and emerging personal stress due to numerous limitations in preaching during the pandemic are the experience that participants expressed in the study. These findings highlight the need for balancing the dynamic relationship between humans and technology while providing a reminder of one the most critical aspect of homiletics, and that is the preacher themselves. Keywords : Homiletics, Pastors, COVID-19 Pandemic, Technology